Pengaruh Daya Tarik Wisata terhadap Minat Kunjung ke Gedung Joang 45 Jakarta Pusat - Valensia Effendy, Valensia Effendy; Rendy Sarudin, Rendy Sarudin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Historical tourism is a tour that is in great demand by tourists and also students, tourists rarely have the intention to visit historical tourism because they think historical tourism is very boring and this makes visitor intensity influential and many museums have implemented the development of digitalization technology which makes it easier for visitors to find out what they want to know about the object. The purpose of this research is to determine the effect of attractiveness on visiting interest. This research was conducted using quantitative methods with this quantitative research researchers will observe quantified phenomena and understand the quantity of a phenomenon that can be used later for comparison and, researchers can see patterns of relationships, interactions, and causality of the observed phenomena. In collecting samples used in this study using purposive sampling techniques, questionnaires as primary data, previous research data, journals, articles, and the internet as secondary data. This study amounted to 100 respondents who had criteria in the form of respondents who had come to the Joang 45 Museum. Static data management in this study uses SPSS software where the results of this data processing will explain the relationship between variable X and variable Y. The results of the tests conducted by the researcher prove that the results of the tests conducted by the researcher prove the relationship between variable X and variable Y. The results of the tests carried out by researchers prove that there is a significant influence of attractiveness on interest in visiting Joang 45 Museum. This is evidenced by the results of the t test with a significance value of 0.000 <0.05 and a tcount value of 10.417 ttable 1.66 in this study stating the significance of the influence of attractiveness on visiting interest. In addition to the t test, there are multicollinearity test results, it is known that the tolerance value is 1,000> 0.10 and the VIF value is 1,000 < 10.00, which means that there is no multicollinearity. And, based on the results of heteroscedasticity with a significance value of 0.598> 0.05, it can be concluded that this research data does not have problems with heteroscedasticity. As for the R2 test of 0.525, which means it can be concluded that there is an influence of variable X to variable Y of 52.5% with the rest being influenced by other variables not contained in this study. Based on the research findings, it can be deduced that the attractiveness factor significantly affects the interest in visiting the Joang 45 Museum. This study is anticipated to serve as a valuable point of reference for stakeholders involved in museum management.